Women of Faith in Victorian Culture - Bradstock, Andrew. author. aut Link
XV, 230 p.
Keywords: An interdisciplinary study of Victorian women of faith as portrayed in the fiction and non-fiction of the period. The book explores how novelists, biographers and other writers depicted religious women, with special reference to the influence of the ideal of the 'Angel in the House' as embodied in Coventry Patmore's poem of that name. Among those whose work is explored are George Eliot, Elizabeth Gaskell, Christina Rossetti, George Moore and Anne Bront as well as hymnwriters, missionary biographers, non-conformist obituarists and artists of the Aesthetic Movement.